Disentangling the Effects of Global and Regional Drivers on Diverse Long‐Term pH Trends in Coastal Waters - Ming Li; Renjian Li; Yijun Guo; Jeremy M. Testa; Wei‐Jun Cai; Chunqi Shen; Yuren Chen; Sujay S. Kaushal (AGU Advances)
Abstract Unlike declines of pH in the open ocean on the total scale (pHT), coastal systems have shown complex long‐term trends in pHT due to a multitude of global and regional drivers. These drivers include changes in nutrient loading, human‐accelerated chemical weathering of watersheds, acid‐rain and land‐use changes, and ocean acidification due to atmospheric CO2 increase. We lack understanding of how these co‐occurring processes have influenced long‐term pHT changes in coastal waters. To address this knowledge gap, a coupled hydrodynamic‐biogeochemical‐carbonate chemistry model was used to conduct a hindcast simulation and scenario analyses of carbonate chemistry in the Chesapeake Bay between 1951 and 2010. Trend analysis reveals increasing pHT in the upper Bay due to river alkalinization but decreasing pHT in the bottom waters of the mid‐and lower Bay due to ocean acidification. No trend is detected in the surface waters of the mid‐ and lower Bay due to competition between the two drivers. The effect of river alkalinization on the acidic volume in the estuary is twice that of ocean acidification. Our findings show that river alkalinization provides an important buffer against acidification while eutrophication plays a secondary role. Our results also suggest ocean alkalinity enhancement could be effective in mitigating acidification in coastal waters.